Implications of Teacher Certification in Realizing Teacher Welfare - Shafira Nurulita Salehuddin; Yudithia Dian Putra; Imron Arifin; Eny Nur Aisyah; Pramono Pramono (Education and Sociedad Journal, 2024)
This study aims to analyze the implications of teacher certification policies in realizing teacher welfare. The research uses a qualitative approach. Data was collected through in-depth observation and interviews with certified, non-certified teachers, and school principals, which were then analyzed through the stages of data condensation, data presentation, and verification. The results of the study show that the certification policy has a positive impact on the fulfillment of economic welfare through professional allowances, encouraging teacher professionalism through competency recognition, and improving social welfare through community recognition. However, this study also found that there is an imbalance in access to certification programs, so that policy effectiveness is not optimal. The implication of this study is the need to improve the accessibility and inclusivity of certification programs to ensure that the benefits of the policy are felt equally by all teachers. This result is expected to be the basis for developing more effective and equitable policies in supporting the welfare of teachers.